Novel CACNA1S mutation causes autosomal dominant hypokalemic periodic paralysis in a South American family (2009)
Hypokalaemic periodic paralysis (HypoPP) is an autosomal dominant disorder, which is characterized by periodic attacks of muscle weakness associated with a decrease in the serum potassium level. A major disease-causing gene for HypoPP has been identified as CACNA1S, which encodes the skeletal muscle calcium channel ?-subunit with four transmembrane domains (I-IV), each with six transmembrane segments (S1-S6). To date, all CACNA1S mutations identified in HypoPP patients are located within the voltage-sensor S4 segment. In this study we report a novel CACNA1S mutation in a new region of the protein, the S3 segment of domain III. We characterized a four-generation South American family with HypoPP. Genetic analysis identified a novel V876E mutation in all HypoPP patients in the family, but not in normal family members or 160 control people. Clinical analysis indicates that mutation V876E is associated with a severe outcome as characterized by a very early age of onset, complete penetrance and a severe prognosis including death. These results identify a new mutation in CACNA1S and expand the spectrum of CACNA1S mutations associated with HypoPP. © 2009 The Japan Society of Human Genetics All rights reserved.